PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CANDANA PUTRA NUSANTARA - Prayogi Abd. Jalil (Manajemen Bisnis, 2018)
This study aims at describing and analyzing the effect of compensation and work discipline toward employees’ work performance especially the production division of PT. Candana Putra Nusantara. This study was conducted by distributing questionnaire to 100 respondents by using Total Sampling Method. The analysis technique applied was range scale and double linear regression. The result of the study shows 1) Employees’ work performance is considered high, compensation is considered medium, and work discipline is medium. 2) Partially, according to the t-test, the compensation had significant effect toward employees’ performance. 3) Work discipline had significant effect toward employees’ performance. 4) the f-test result showed that compensation and work discipline had significant effect toward employees’ work performance, and 5) Compensation as a stronger variable in affecting employees’ work performance. Company is suggested to pay attention more on the compensation by providing salary based on Minimum Wage of Probolinggo and improving work discipline especially toward the company’s regulation.